2011
DOI: 10.1074/mcp.m110.002188
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy to Isolate Ubiquitin Conjugates Reveals Wide Role for Ubiquitination during Neural Development

Abstract: Ubiquitination has essential roles in neuronal development and function. Ubiquitin proteomics studies on yeast and HeLa cells have proven very informative, but there still is a gap regarding neuronal tissue-specific ubiquitination. In an organism context, direct evidence for the ubiquitination of neuronal proteins is even scarcer. Here, we report a novel proteomics strategy based on the in vivo biotinylation of ubiquitin to isolate ubiquitin conjugates from the neurons of Drosophila melanogaster embryos. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
107
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 97 publications
5
107
1
3
Order By: Relevance
“…With this goal in mind we adopted a system for in vivo tagging of ubiquitin chains with biotin, previously used to identify ubiquitin-conjugated proteins from the Drosophila neural system (30), and applied it to a human cell line (U2OS) that can be tightly synchronized at mitosis. In contrast to several recent studies that employed antibodies specific to the diGly-Lys remnant that marks ubiquitination sites following trypsin digestion (19,25), an in vivo ubiquitin tagging strategy allows direct validation of candidate ubiquitinated proteins (whether mono-or polyubiquitinated) through immunoblotting of samples.…”
mentioning
confidence: 99%
“…With this goal in mind we adopted a system for in vivo tagging of ubiquitin chains with biotin, previously used to identify ubiquitin-conjugated proteins from the Drosophila neural system (30), and applied it to a human cell line (U2OS) that can be tightly synchronized at mitosis. In contrast to several recent studies that employed antibodies specific to the diGly-Lys remnant that marks ubiquitination sites following trypsin digestion (19,25), an in vivo ubiquitin tagging strategy allows direct validation of candidate ubiquitinated proteins (whether mono-or polyubiquitinated) through immunoblotting of samples.…”
mentioning
confidence: 99%
“…Proteomic experiments designed to identify ubiquitinated proteins have primarily used epitope-tagged ubiquitin (15)(16)(17)(18)(19)(20)(21)(22) or ubiquitin affinity methods (23)(24)(25)(26)(27). However, because NAE inhibition blocks the ubiquitination of a minor subset of pro-teasome substrates, approaches relying on changes in global ubiquitination are unlikely to sufficiently enrich NAE-dependent changes.…”
mentioning
confidence: 99%
“…The birAubiquitin is then incorporated into the ubiquitin-chains allowing the pull-down of biotinubiqutinated substrates using streptavidin or avidin-beads. Coupled to mass-spectrometric analysis, this study identified several hundred ubiquitinated substrates [85][86][87].…”
Section: Bio-ubiquitinmentioning
confidence: 99%